2018
DOI: 10.5194/acp-18-6075-2018
|View full text |Cite
|
Sign up to set email alerts
|

Decadal evolution of ship emissions in China from 2004 to 2013 by using an integrated AIS-based approach and projection to 2040

Abstract: Abstract. Ship emissions contribute significantly to air pollution and pose health risks to residents of coastal areas in China, but the current research remains incomplete and coarse due to data availability and inaccuracy in estimation methods. In this study, an integrated approach based on the Automatic Identification System (AIS) was developed to address this problem. This approach utilized detailed information from AIS and cargo turnover and the vessel calling number information and is thereby capable of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 24 publications
1
25
1
Order By: Relevance
“…The annual SO2, PM, NOx and HC emissions from ships within 200 Nm to the coastline of China in 2013 were 918.4, 119.3, 1380.9 and 49.3 kt. The emissions were slightly lower than those reported by Li et al (2018), probably due to the differences in emission factors, AIS data and ship registration database. 15The increase of shipping emissions near the coast of China was probably small from 2013 to 2015, because the global CO2 emissions from ships only increased by 2.5% over that period (ICCT, 2017).…”
Section: Temporal and Spatial Variations Of Shipping Emissionscontrasting
confidence: 63%
“…The annual SO2, PM, NOx and HC emissions from ships within 200 Nm to the coastline of China in 2013 were 918.4, 119.3, 1380.9 and 49.3 kt. The emissions were slightly lower than those reported by Li et al (2018), probably due to the differences in emission factors, AIS data and ship registration database. 15The increase of shipping emissions near the coast of China was probably small from 2013 to 2015, because the global CO2 emissions from ships only increased by 2.5% over that period (ICCT, 2017).…”
Section: Temporal and Spatial Variations Of Shipping Emissionscontrasting
confidence: 63%
“…The emission factors used in V and Ni emission estimates were updated to five classification schemes described in Text of the supporting information with Tables S1 and S2, and the details of the method and value of low‐load adjustment multipliers and control factors can be found in our previous studies (Fan et al., 2016; Feng et al., 2019). Average sulfur content for HFO and MDO fuel was set to 2.7% and 0.5% (Chen et al., 2017; Feng et al., 2019; Li et al., 2018a; Ng et al., 2013). According to the China Marine Bunker's statistic data (Fan et al., 2016; Feng et al., 2019), we allocated the fuel oil types for low/medium/high speed engines and choose the emission factors of V and Ni according to the oil types for calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Chen et al [56] suggested the application of clean energy sources in the Pearl River Delta with AIS-based emission assessment. Based on the integrated AIS-based method, Li et al [57] made a decadal assessment for Chinese ship emissions from 2004 to 2013. AIS big data was also applied to calculate ship emissions in the Port of Rio de Janeiro, Brazil [58].…”
Section: Research Demandmentioning
confidence: 99%
“…Besides, the full AIS database is not opened freely for public access, especially in the East Asia region. The AIS data before 2012 was also not good due to the lack of satellites and shore-based radars [57]. Sun [60] suggested the application of big data analysis technology to overcome the limitations of AIS.…”
Section: Research Demandmentioning
confidence: 99%